1995
DOI: 10.1007/bf00300024
|View full text |Cite
|
Sign up to set email alerts
|

Determination of heparan sulphate in kidney tissues of patients with calcium nephrolithiasis

Abstract: While the pathogenic mechanisms responsible for calcium nephrolithiasis remain unknown, the influence of heparan sulphate proteoglycan (HSPG) on disease progression of other diseases, such as polycystic kidneys and diabetic glomerulosclerosis, makes it an important candidate for the study of stone formation. Using the indirect immunofluorescence assay and image analysis, we were able to quantify and visualize the loss of HSPG localized in the basement membrane of the glomerulus and the mucosa of ureter or rena… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

1997
1997
2008
2008

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 9 publications
0
3
0
Order By: Relevance
“…However, the level of HS-PG mRNA expression was significantly higher in SF rats than in normal rats. Basement membrane HS-PG levels in urolithiasis were investigated by Chan and Tan [5], who reported a significant decrease of HS-PG in the GBM and upper urinary tract. However, they did not find significant changes in HS-PG in the TBM between patients with stones and normal controls [5].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…However, the level of HS-PG mRNA expression was significantly higher in SF rats than in normal rats. Basement membrane HS-PG levels in urolithiasis were investigated by Chan and Tan [5], who reported a significant decrease of HS-PG in the GBM and upper urinary tract. However, they did not find significant changes in HS-PG in the TBM between patients with stones and normal controls [5].…”
Section: Discussionmentioning
confidence: 99%
“…Basement membrane HS-PG levels in urolithiasis were investigated by Chan and Tan [5], who reported a significant decrease of HS-PG in the GBM and upper urinary tract. However, they did not find significant changes in HS-PG in the TBM between patients with stones and normal controls [5]. Nishio et al [17] also reported that HS levels increased in rat renal tubules during microlith formation.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation